Blue Car, Red Car: Developing Efficiency in Online Interpretation of Adjective-Noun Phrases - Fernald, Anne (2010)
Two experiments investigated the development of fluency in interpreting adjective-noun phrases in 30- and 36-month-old English-learning children. Using online processing measures, children’s gaze patterns were monitored as they heard the familiar adjective/noun phrases (e.g. blue car) in visual contexts where the adjective was either informative (e.g. blue car paired with red car or red house) or uninformative (e.g. blue car paired with blue house). Thirty-six-month-olds processed adjective-noun phrases incrementally as adults do, orienting more quickly to the target picture on informative-adjective trials than on control trials. Thirty-month-olds did not make incremental use of informative adjectives, and experienced disruption on trials when the two potential referents were identical in kind. In the younger children, difficulty in integrating prenominal adjectives with the subsequent noun was associated with slower processing speed across conditions. These findings provide evidence that skill in putting color word knowledge to use in real-time language processing emerges gradually over the third year.